Red Rosella (Hibiscus sabdariffa Linn.) Petal Brew is Able to Reduce the Sprague Dawley MDA Rate in Rats Exposed to Waste Cooking Oil - Ulilalbab, Arya; Maskanah, Eni (Folia Medica Indonesiana, 2018)
Food and snacks sold are usually fried using oil that has been used for frying repeatedly. Oil that is repeatedly used for frying is often called waste cooking oil. Waste cooking oil is a source of exogenous free radicals that can trigger oxidative stress. To prevent this, sufficient antioxidant intake is needed. One source of antioxidants is red rosella. The purpose of this study was to analyze the effect of giving red rosella petals on the conditions of oxidative stress in Sprague dawley rats exposed to waste cooking oil through MDA testing. The research method used was Completely Randomized Design (CRD). The sample consisted of 24 male rats which were randomly selected and divided into 4 groups: negative control (no treatment), positive control (administered with waste cooking oil of 8.92 meq/kg as much as 2 ml/kgBW), treatment 1 (administered with waste cooking oil of 8.92 meq/kg as much as 2 ml/kgBW and red rosella petal brew dosed of 540 mg/kgBW, and treatment 2 (administered with waste cooking oil of 8.92 meq/kg as much as 2 ml/kgBW and red rosella petals brew dosed of 810 mg/kgBW). The results of the one way ANOVA analysis (a=1%) and the Tukey HSD test showed the p value of MDA=0.00, indicating that all treatments had significant effect. In further tests, it was found that all treatments contained differences in MDA values. The best value in the treatment was by giving a dose of 810 mg/kgBW (serum MDA of 2.22 nmol/ml). It can be concluded that the administration of red rosella petal in doses of 540 mg/kgBW (EC50=407.52 ppm) and 810 mg/kgBW (EC50=247.82 ppm) can improve the oxidative stress of Sprague dawley rats.